Implementing Project-Based Learning in Islamic Religious Education to Develop Students' Islamic Creativity - Amaliah, Zakiah; Ridwan, Ahmad; Putra, Darma (Yayasan Rahmat Islamiyah, 2025)
This study aimed to analyze and identify obstacles to the development of students' Islamic creativity at SMP Negeri 2 Reteh in Islamic Religious Education lessons using project-based learning. This study used a qualitative approach with descriptive phenomenology. Data collection techniques included observation, interviews, and documentation. The results showed that the implementation of project-based learning had a positive impact on the development of students' Islamic creativity, particularly in aspects of responsibility, honesty, self-confidence, and active participation in the learning process. Students were able to discuss, convey ideas, and complete projects effectively. Challenges faced by teachers included time management, lack of supporting facilities, and differences in student ability levels. Thus, project-based learning has proven to be an effective learning alternative for developing students' Islamic creativity in secondary schools.